General St. Gallen-2015 guidelines for the treatment of early breast cancer (adapted by the experts of the Russian Society of Breast Oncologists) - V. F. Semiglazov; R. M. Paltuev; V. V. Semiglazov; G. A. Dashyan; T. Yu. Semiglazova; P. V. Krivorotko; K. S. Nikolaev (Опухоли женской репродуктивной системы)
General St. Gallen-2015 guidelines for the treatment of early breast cancer (adapted by the experts of the Russian Society of Breast Oncologists)